The mediating role of mentalizing capacity between parents and peer attachment and adolescent borderline personality disorder. Issue 1 (December 2017) - Beck, Emma; Sharp, Carla; Poulsen, Stig; Bo, Sune; Pedersen, Jesper; Simonsen, Erik
Abstract Background Insecure attachment is a precursor and correlate of borderline personality disorder. According to the mentalization-based theory of borderline personality disorder, the presence of insecure attachment derails the development of the capacity to mentalize, potentially resulting in borderline pathology. While one prior study found support for this notion in adolescents, it neglected a focus on peer attachment. Separation from primary caregivers and formation of stronger bonds to peers are key developmental achievements during adolescence and peer attachment warrants attention as a separate concept. Findings In a cross-sectional study, female outpatients (Mage 15.78=, SD = 1.04) who fulfilled DSM-5 criteria for BPD (N = 106) or met at least 4 BPD criteria (N = 4) completed self-reports on attachment to parents and peers, mentalizing capacity (reflective function) and borderline personality features. Our findings suggest that in a simple mediational model, mentalizing capacity mediated the relation between attachment to peers and borderline features. In the case of attachment to parents, the mediational model was not significant. Conclusions The current study is the first to evaluate this mediational model with parent and peer attachment as separate concepts and the first to do so in a sample of adolescents who meet full or sub-threshold criteria for borderline personality disorder. Findings incrementally support that mentalizing capacity and attachment insecurity, also in relation to peers, are important concepts in theoretical approaches to the development of borderline personality disorder in adolescence. Clinical implications are discussed.